Energy portal for HVAC applications via smart phones - Hongamornsin, Supphavit (2013)
Indoor positioning systems (IPS) are seeing more interest and research in recent years. However, such systems require wireless sensor networks to be set up to facilitate the positioning computations of the desired object.